2022
DOI: 10.20944/preprints202212.0522.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using HyperLogLog to Prevent Data Retention in Social Media Streaming Data Analytics

Abstract: Social media data is widely used to gain insights about social incidents, whether on a local or global scale. Within the process of analyzing and evaluating the data, it is common practice to download and store it locally. Considerations about privacy protection of social media users are often neglected thereby. However, protecting privacy when dealing with personal data is demanded by laws and ethics. In this paper we introduce a method to store social media data using the cardinality estimator HyperLogLog. B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…HyperLogLog (HLL) has been proposed as a base sketch to provide privacy too (e.g., [20]) that can be applied to, for instance, social media data processing in disaster management [21]. In [22], the authors have concluded that cardinality estimators, which are used for aggregation (e.g., HLL sketches that are merged by data analysis tools) and consequently require accuracy, do not preserve privacy.…”
Section: Privacy and Sketchesmentioning
confidence: 99%
“…HyperLogLog (HLL) has been proposed as a base sketch to provide privacy too (e.g., [20]) that can be applied to, for instance, social media data processing in disaster management [21]. In [22], the authors have concluded that cardinality estimators, which are used for aggregation (e.g., HLL sketches that are merged by data analysis tools) and consequently require accuracy, do not preserve privacy.…”
Section: Privacy and Sketchesmentioning
confidence: 99%